Binkle and flip misbehave - Blyton, Enid (Award Publications Limited London, 2010)
Flip Misbehave is a whimsical children's story about a mischievous character named Flip, who loves causing trouble and bending the rules. Despite the constant warnings from his friends and family, Flip continues to misbehave, creating chaos wherever he goes. However, when his antics backfire, Flip learns valuable lessons about responsibility, respect, and the consequences of his actions. Through humor and light-hearted storytelling, the book teaches young readers about the importance of good behavior and the impact it has on others.